Health Education to Improve Knowledge of Adequate Water Intake for Kidney Health - Harun, Hasniatisari; Maryani, Yani; Pebrianti, Sandra; Agung, Rizki Nugraha (Universitas Padjadjaran, 2026)
Adequate hydration is essential for maintaining kidney function and physiological balance. However, awareness of sufficient daily water intake as a preventive health behavior remains limited, particularly among patients and family caregivers in hospital settings. Improving hydration knowledge through educational interventions may contribute to early prevention of kidney health problems. This community service program implemented a pre–post educational intervention in a hospital setting involving 66 participants consisting of patients and their family caregivers. Health education was delivered through interactive lectures, discussions, and educational leaflets focusing on recommended daily water intake and the role of hydration in maintaining kidney health. Knowledge was measured using a researcher-developed questionnaire consisting of five questions related to adequate water consumption. Data were analyzed using descriptive statistics and paired sample t-test. Participants’ knowledge improved significantly after the intervention. The mean knowledge score increased from 63.63 ± 20.12 at pretest to 94.54 ± 12.31 at posttest. Statistical analysis confirmed a significant difference between measurements (mean difference = −30.91; t = −10.85; df = 65; p < 0.001). Hospital-based hydration education effectively improves knowledge regarding adequate water intake. This intervention may serve as a simple and scalable strategy for integrating kidney health promotion into routine hospital education programs. Keywords: Adequate water intake, hydration education, kidney health, patient knowledge